2010
DOI: 10.12934/jkpmhn.2010.19.1.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Insight and Empowerment on Function and Quality of Life for Patients with Schizophrenia.

Abstract: PURPOSE: The purpose of this study was to examine whether insight and empowerment had a positive impact on function and quality of life for patients with schizophrenia. METHODS: The subjects consisted of 446 patients with schizophrenia who were attending 20 psychosocial rehabilitation centers. Data were analyzed by the SPSS/WIN and AMOS programs. RESULTS: Insight showed a direct effect on empowerment, function, and quality of life for patients with schizophrenia. Empowerment showed a direct effect on function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
2
0
2
Order By: Relevance
“…The results of this study indicate that global function predicts empowerment, which then predicts personal recovery. Empowerment was determined as a mediator, which is consistent with the findings of previous studies [ 32 34 ]. Our study shows that empowerment mediates the relationship between global function and personal recovery, and we can target empowerment in an attempt to reduce the impact global function has on personal recovery.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of this study indicate that global function predicts empowerment, which then predicts personal recovery. Empowerment was determined as a mediator, which is consistent with the findings of previous studies [ 32 34 ]. Our study shows that empowerment mediates the relationship between global function and personal recovery, and we can target empowerment in an attempt to reduce the impact global function has on personal recovery.…”
Section: Discussionsupporting
confidence: 87%
“…Empowerment mainly entails promoting patient autonomy, independent decision-making and responsibility, and self-management [ 30 , 31 ]. Additionally, empowerment can mediate the association between the function and quality of life in patients with schizophrenia [ 32 34 ], the association between the in-group perceptions and personal recovery among people with mental illness [ 32 ], and the association between rehabilitation activities and quality of community-based life for people with schizophrenia [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Empowerment mainly entails promoting patient autonomy, independent decision making and responsibility, and self-management [25,26]. Evidence has shown that empowerment can play a mediating role in improving quality of life, hopelessness, or recovery among individuals with schizophrenia [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…정신장애인의 역량을 강화하는 요소로 자존감, 의 사결정 등의 향상을 보고하나 (Kim & Park, 2010;Ko et al, 2008), 전문가의 중재에 의한 역량강화 프로그램이 정신장애 인의 부정적인 개념인 내재화된 낙인에 대한 효과를 입증하지 못하였다 (Ko et al, 2008). 이것은 정신장애인의 주도성에 대 한 개념이 명확하지 않은 상태에서 전문가의 중재로 정신장애 인에게 역량강화 프로그램을 제공하였기 때문이다.…”
unclassified
“…이것은 정신장애인의 주도성에 대 한 개념이 명확하지 않은 상태에서 전문가의 중재로 정신장애 인에게 역량강화 프로그램을 제공하였기 때문이다. 그렇지만 정신장애인은 역량강화를 통해 직업재활과 지역사회 통합을 달성하여 독립적인 생활과 삶의 질을 향상시킬 수 있으며 (Kim & Park, 2010), 정신장애인 스스로가 주도성을 발휘하 면서 더불어 역량강화가 이루어질 수 있다 (Koo, 2011).…”
unclassified